Quantitative inheritance properties for simultaneous approximation by tensor product operators II: Applications - Beutel, Laura; Gonska, Heiner (J. Numer. Anal. Approx. Theory, 2021)
We summarize several general results concerning quantitative inheritance properties for simultaneous approximation by tensor product operators and apply these to various situations. All inequalities are given in terms of moduli of continuity of higher order.